THE EFFECTIVENESS OF THE SQ4R METHOD IN ENHANCING READING COMPREHENSION OF DESCRIPTIVE TEXTS AMONG GRADE X TKJ STUDENTS AT SMK PGRI 1 NGANJUK - Mutiara Elva Ardhani; Anita Budi Rahayu (Universitas PGRI Mpu Sindok, 2026)
This study aims to investigate the effectiveness of the SQ4R (Survey, Question, Read, Reflect, Recite, and Review) method in enhancing students’ reading comprehension of descriptive texts among Grade X TKJ students at SMK PGRI 1 Nganjuk in the academic year 2024/2025. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group. The sample consisted of 80 students divided into two groups: experimental and control. The research instrument was an essay-based reading comprehension test comprising 10 questions. Data were analyzed using an independent sample t-test, which revealed a significance value (Sig. 2-tailed) of 0.006 (<0.05), indicating a significant difference between the two groups. These findings confirm that the SQ4R method effectively improves students’ reading comprehension of descriptive texts. It is recommended that English teachers adopt this method to foster active engagement and better comprehension in reading lessons.